1993
DOI: 10.1002/app.1993.070500307
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase polymerization of ethylene using MgCl2/ethyl benzoate/TiCl4 + triethylaluminum catalyst: Effects of triethylaluminum and temperature

Abstract: A gas-phase reactor system was developed to polymerize ethylene using the MgC12/ethyl benzoate (EB)/TiC1, + triethylaluminum (TEA) catalyst. The reproducibility of the reactor was tested and found to be adequate for kinetic study. The effects of TEA and temperature were studied with the multisite model that assumes a multiplicity of active sites. It was found that the productivity increased with Al/Ti molar ratio while initial activity leveled off. The deactivation rate, after an initial increase, decreased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…It is intriguing to observe that remaining catalyst variables do not seem to exert any influence upon the final quality of the polymer resin and catalyst productivity. Polymer yield is assumed to be of first order in respect to catalyst concentration and solubles and XO are assumed to be functions of the A/T ratio used during both the catalyst preparation and the polymerization reaction 21–23. These effects may be due do the large influence of temperature upon the polymerization results and due to the narrow ranges of variation of the catalyst variables, as imposed by plant operation constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intriguing to observe that remaining catalyst variables do not seem to exert any influence upon the final quality of the polymer resin and catalyst productivity. Polymer yield is assumed to be of first order in respect to catalyst concentration and solubles and XO are assumed to be functions of the A/T ratio used during both the catalyst preparation and the polymerization reaction 21–23. These effects may be due do the large influence of temperature upon the polymerization results and due to the narrow ranges of variation of the catalyst variables, as imposed by plant operation constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The sixth variable is the batch time (1 < t < 3 h), included in the experimental design to allow the evaluation of the well‐known catalyst decay 11. The seventh variable is the amount of alkyl‐aluminum added to the reaction environment during polymerization, evaluated as the Al/Ti ratio (1.4 < A/T 2 < 2), expected to influence both catalyst activity and the average molecular weight of the final polymer resin 23. The experimental ranges selected in all cases are in accordance with actual industrial operation conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Using the yield data, maximum activity is much higher (ú90). 31 If the r c has been estimated to be around 0.02-0.04 mm.…”
Section: Rate Enhancement Effectmentioning
confidence: 99%
“…Its role in the transition metal oxiSince the discovery of high-activity-supported titanium catalysts, intensive research efforts have been dation state reduction has been widely demonstrated through both physical analysis and chemdirected toward a comprehensive understanding of their structure and kinetic behavior. [1][2][3] In spite of ical measurements. Using techniques such as electron spin resonance spectrometry (ESR), 4 their successful applications in industrial practice, a complete knowledge of these catalyst systems is photometry, 5 chemical ionization-mass spectrometry (CI-MS), 6 X-ray absorption spectrosstill lacking.…”
Section: Introductionmentioning
confidence: 97%